Implementación de un sistema de control interno en la asociación artesanal de comerciantes de leche del cantón Sigchos (asocolesig), periodo 2016 - Tello Tocte, Luis Fernando (2016)
The internal control has evolved over the last decades, which has arisen by the urgent need to solve the problems, productive, commercial and management; such as the merchants association of milk the Sigchos canton "ASOCOLESIG", which since its foundation did not have an internal control system to ensure the development and completion of administrative and operational activities due to lack of budget. So we proceeded to carry out research applying methods, techniques and scientific instruments that help to know the weaknesses and shortcomings of the administrative and operational processes of the organization, it was therefore necessary to implement an internal control system….